2017
DOI: 10.1088/2053-1583/aa6917
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of critical temperature enhancement in atomically thin superconductors

Abstract: Recent experiments showed that thinning gallium, iron selenide and 2H tantalum disulfide to single/several monoatomic layer(s) enhances their superconducting critical temperatures.Here, we characterize these superconductors by extracting the absolute values of the London penetration depth, the superconducting energy gap, and the relative jump in specific heat at the transition temperature from their self-field critical currents. Our central finding is that the enhancement in transition temperature for these ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 76 publications
(203 reference statements)
10
68
0
Order By: Relevance
“…Deduced (0) = 740 ± 3 nm is similar to (0) = 690-850 nm measured for samples possessing maximal Tc values for cuprate counterpart La1-xSrxCuO2 [37]. By utilizing deduced (0) value the Ginzburg-Landau parameter = λ(0) (0) = 130 which is similar to La1-xSrxCuO2 [33,37] and this value is at the upper-level range for other cuprates and unconventional superconductors [15,23,24,26,[38][39][40][41][42][43]. Table I.…”
Section: Jc(sft) Analysissupporting
confidence: 74%
See 2 more Smart Citations
“…Deduced (0) = 740 ± 3 nm is similar to (0) = 690-850 nm measured for samples possessing maximal Tc values for cuprate counterpart La1-xSrxCuO2 [37]. By utilizing deduced (0) value the Ginzburg-Landau parameter = λ(0) (0) = 130 which is similar to La1-xSrxCuO2 [33,37] and this value is at the upper-level range for other cuprates and unconventional superconductors [15,23,24,26,[38][39][40][41][42][43]. Table I.…”
Section: Jc(sft) Analysissupporting
confidence: 74%
“…There is an alternative way to deduce (0), C/C, Tc and 2Δ(0) by the fit of experimental self-field critical current density, Jc(sf,T), to universal equation, which is for thin-film superconductors reduced to simple form [23,24]:…”
Section: Models Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have to note that several intrinsic superconductors exhibit multiple-band superconducting gapping [50,52] and the enhancement of the transition temperature [52][53][54][55][56][57][58][59] when the condition of 2b < c(0) [52] is satisfied. The first discovered material in this class of superconductors is atomically thin FeSe [53][54][55] in which 13-fold increase (i.e., 100 K vs 7.5 K) was experimentally registered to date.…”
Section: Introductionmentioning
confidence: 99%
“…Another milestone experimental finding in this field was reported by Liao et al [9] who observed the effect of new superconducting band opening and Tc enhancement in few layer stanene (which is the closest counterpart of graphene) by tuning the films thicknesses. To date, maximal Tc increase due to the effect [52], stands with another single-atomic layer superconductor, Td-MoTe2, for which Rhodes et al [59] reported 30-fold Tc increase when samples were thinning down to single atomic layer.…”
Section: Introductionmentioning
confidence: 99%